2022
DOI: 10.3390/ijerph192113996
|View full text |Cite
|
Sign up to set email alerts
|

Sodium Nitrite Intoxication and Death: Summarizing Evidence to Facilitate Diagnosis

Abstract: Background: Over the years, forensic pathology has registered the spread of new methods of suicide, such as the ingestion of sodium nitrite. Sodium nitrite causes increased methemoglobin, resulting in systemic hypoxia, metabolic acidosis, and cyanosis. Since sodium nitrite is a preservative, the ingestion of foods containing an excessive amount of this substance can also cause acute intoxication up to death. The present review is aimed at guiding health professionals in the identification and management of sod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 68 publications
1
17
0
Order By: Relevance
“…From this point of view, in fact, the role of pathology and forensic toxicology must not end at the collection and documentation of scientific evidence for justice purposes, but should also guarantee the provision of a window on some underestimated social and health problems in order to address the necessary social and health policies [ 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…From this point of view, in fact, the role of pathology and forensic toxicology must not end at the collection and documentation of scientific evidence for justice purposes, but should also guarantee the provision of a window on some underestimated social and health problems in order to address the necessary social and health policies [ 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…17,18 In one literature review, researchers accessed a limited number of psychiatric histories in cases of intentional nitrite ingestion. 11 These histories included depression (70%), previous suicide attempts (60%), bipolar disorder (20%), schizophrenia (10%), paranoia (10%), previous self-harm attempts…”
Section: Suicide By Sodium Nitritementioning
confidence: 99%
“…Case reports from the US, Japan, and Korea have also confirmed that sodium nitrite is being ingested as a means of suicide 19-25. In 2022, researchers surveyed this literature for cases of sodium nitrite ingestion 11. Their review identified 132 cases, 53 of which were for suicidal purposes.…”
Section: Suicide By Sodium Nitritementioning
confidence: 99%
See 2 more Smart Citations